Anti-multiple nuclear dots (anti-MND) and anti-SP100 antibodies in hepatic and rheumatological disorders - Muratori, P (Blackwell Science Inc, 2002)
Multiple nuclear dots pattern has been described in primary biliary cirrhosis and, less often, in rheumatological disorders. Sp100 is the major antigen of multiple nuclear dots. We evaluated prevalence and diagnostic significance of multiple nuclear dots and anti-Sp100 reactivity both in hepatic and rheumatological diseases. A series of 283 consecutive liver patients (89 primary biliary cirrhosis, 12 primary sclerosing cholangitis, 85 autoimmune hepatitis, 97 hepatitis C virus-related chronic liver disease) and of 89 consecutive rheumatological cases were evaluated. Presence of multiple nuclear dots was assessed by indirect immunofluorescence on HEp-2 cells, anti-Sp100 reactivity by ELISA with recombinant protein. Multiple nuclear dots were detected in 20 patients (7%) with liver disease (of whom 15 with primary biliary cirrhosis), and in eight patients (9%) with rheumatological disorders. Anti-Sp100 was detected in 45 liver patients (16%), of whom 30 with primary biliary cirrhosis, but in only two with rheumatological disorders (2%) (P = 0·0004). The concordance between multiple nuclear dots and anti-Sp100 in liver and rheumatological patients was 90% and 25% (P = 0·0018), respectively. Among 89 consecutive patients with primary biliary cirrhosis, multiple nuclear dots and anti-Sp100 were present in 17% and 34%, respectively (P = 0·0152). Anti-Sp100 positivity was associated with older age and higher gamma-globulin levels. Multiple nuclear dots are similarly observed in liver and rheumatological patients. In contrast, anti-Sp100 is more frequent in liver patients and is significantly more often detected in primary biliary cirrhosis, of which it can be regarded as a highly specific serological marker. The antigenic target of multiple nuclear dots in most rheumatological patients is other than Sp100.